Sporting Resilience During COVID-19: What Is the Nature of This Adversity and How Are Competitive Elite Athletes Adapting? - Gupta, Sahen; McCarthy, Paul Joseph (Frontiers in Psychology, 2021)
The COVID-19 pandemic is a global health issue which has severely disrupted and deferred several landmark international sporting competitions. Like the general population, athletes have faced direct psychological consequences from COVID-19 in addition to cancelation of events, loss of support, lack of training, loss of earnings, hypervigilance, and anxiety among others. The aim of the present research was to identify the adversity experiences of athletes caused by COVID-19 (study 1) and explore the process of resilience used by competitive elite athletes for positive adaptation (study 2). Research has indicated psychological resilience to be a protective factor against similar adversities in the sporting context. The study uses an across-cases qualitative design comparing the real-time lived experiences of athletes during COVID-19 using narrative analysis. Data were collected from 10 competitive elite athletes from various countries, as part of a larger doctoral dissertation study during the lockdown period, using in-depth experiential interviews. Study 1 presents detailed narratives on the loss and incongruence, which were the two major adversities experienced. Study 2 outlines the process of resilience as narrated by the participants through the emergent and minimal-impact resilience trajectories. We discuss recommendations for interventions and the role of sports psychologists, coaches, and sporting organizations in ensuring athletes’ mental health and their rehabilitation into post-COVID sports life.